A simple and rapid molecular detection of Staphylococcus aureus strain B using multiplex PCR - Sheikhi, Fatemeh; Zeinoddini, Mehdi; Samimi Nemati, Afshin; Veysi, Saeed (Chulalongkorn Medical Journal, 2020)
Background: Staphylococcucs aureus (S. aureus) is one of the most important and pathogenic species from the Staphylococcaceae family. S. aureus is capable of producing several enterotoxins (SEs) that are classified in different groups from A-R. Objective: The present study aimed to set up simple and rapid detection of S. aureus strain B to develop a multiplex polymerase chain reaction (PCR) assay for the identification of genus and strain B of this bacterium. Methods: In this work, after designing specific primers for 23S rRNA and SEB, one step multiplex PCR was carried out and the PCR product analyzed by agarose gel electrophoresis. The specificity of this method was determined using different strains of S. aureus A (SEA), S.aureus C (SEC), Bacillus subtilis, Bacillus cereus, and Listeria monocytogenes. Also, the sensitivity was distinguished by serial dilution of the DNA genome from S. aureus. Results: The PCR product was indicated at 226 and 1,250 bp specific amplified fragments according to amplification of SEB and 23SrRNA, respectively. The sensitivity of this method determined about 2 103 CFU/ml and also the results showed that according to specific primers, the PCR is very specific. Conclusion: This multiplex PCR assay can be used as a simple diagnostic test in clinical laboratories for identification of S. aureus.